Predicting family violence recidivism using the DVSI-R: integrating survival analysis and perpetrator characteristics - Stansfield, Richard (Criminal justice and behavior, 2014)
Recent published predictive validation studies of risk assessment instruments commonly used the explanatory power of Receiver Operating Characteristics (ROC) analysis. The present study also tested the predictive validity of the Revised Domestic Violence Screening Instrument (DVSI-R) by conducting a ROC analysis of 18-month follow-up data post assessment from the entire state of Connecticut between January 1, 2010, and May 31, 2012. With a sample of 29,317, the analysis examined rearrests for new family violence incidents and new violations of protective or restraining orders. The sample was predominantly male (70%), with an average age of 34 years, and equally split between non-Latino White and minority perpetrators. Moving beyond the explanatory power of ROC analysis, the Kaplan?Meier (KM) estimator of the survival function was used to examine the cumulative probability of rearrest during the time at-risk period. In addition to determining the survival functions of perpetrators based on their level of risk as identified by their DVSI-R total numeric risk scores, the analysis examined differences by characteristics of perpetrators, an issue given scant attention in prior research. Survival analyses identified critical times after intake assessments when those who reoffended were at greatest risk and significant differences in timing of reoffending by gender and ethnicity. Implications for intervention are discussed.